Codes for digital recorders - Schouhamer Immink, K.E.; Siegel, P.H.; Wolf, J.K. (IEEE transactions on information theory, 1998)
Constrained codes are a key component in digital recording devices that have become ubiquitous in computer data storage and electronic entertainment applications. This paper surveys the theory and practice of constrained coding, tracing the evolution of the subject from its origins in Shannon's classic 1948 paper to present-day applications in high-density digital recorders. Open problems and future research directions are also addressed.